The concept and legal nature of cross-border merger of companies - Godlewski, Robert (Journal of the Belarusian State University. Law, 2020)
The article deals with the terms «cross-border merger» and «cross-border mergers and acquisitions». The author analyses the term «mergers and acquisitions» in the economic and legal literature, the legal regulation of cross-border mergers and cross-border mergers and acquisitions in the Republic of Belarus, and makes a comparative analysis of cross-border mergersʼ legal regulation by the law of the European Union, Delaware (as a representative of the US law), Switzerland, India. The objective of the article is a comprehensive analysis of the category «cross-border merger». The scientific novelty of the article is the formulation of the definitions of «cross-border merger» and «cross-border mergers and acquisitions», as well as the determination of the cross-border mergers’ legal nature. The article can be useful for students and postgraduates studying corporate relations in international private law.
Keywords: international private law; cross-border mergers and acquisitions; mergers and acquisitions; cross-border mergers; direct investments